Skinfold thickness variation and associations with cardiorespiratory fitness in male soccer players of different ages - Nikolaidis, P T; Weiss, K; Knechtle, B (European review for medical and pharmacological sciences, 2023)
The aim of the present study was to examine skinfold thickness (SKF) distribution in youth and adult male soccer players regarding cardiorespiratory fitness (CRF) and the role of age. Participants were youth [n=83, age 16.2 (1.0) years, mean (standard deviation)] and adult male soccer players [n=121, 23.2 (4.3) years], who were tested for SKF on 10 anatomical sites and Conconi test was used to assess velocity at maximal oxygen uptake (vVO2max). A between-within-subjects analysis of variance revealed a small interaction between the anatomical site and age group on SKF (p=0.006, η2=0.022), where adolescents had larger cheek (+0.7 mm; p=0.022; 95% confidence intervals - CI  - 0.1, 1.3), triceps (+0.9 mm; p=0.017; 95% CI 0.2, 1.6) and calf (+0.9 mm; p=0.014; 95% CI 0.2, 1.5) SKF, while adults had larger chin (+0.5 mm; p=0.007; 95% CI 0.1, 0.8) SKF, and no difference was observed for the rest of the anatomical sites. No difference between adolescent and adult age groups was observed in average SKF (SKFavg) [9.0 (2.7) vs. 9.1 (2.5) mm; difference -0.1 mm; 95% CI, -0.8, 0.6; p=0.738]. Compared to adults, adolescents had a lower SKF coefficient of variation (SKFcv) [0.34 (0.10) vs. 0.37 (0.09); difference-0.03; 95% CI, -0.06, -0.01; p=0.020] and subscapular-to-triceps ration (STR) [1.08 (0.28) vs. 1.29 (0.37); difference-0.21; 95% CI, -0.31, -0.12; p<0.001]. The largest Pearson moment correlation coefficient between vVO2max and SKF was shown in the subscapular (r=-0.411; 95% CI, -0.537, -0.284; p<0.001) and the smallest in the patellar anatomical site (r=-0.221; 95% CI, -0.356, -0.085; p=0.002). In addition, vVO2max correlated moderately with SKFavg (r=-0.390; 95% CI, -0.517, -0.262; p<0.001) and SKFcv (r=-0.334; 95% CI, -0.464, -0.203; p<0.001). In summary, CRF was related to the thickness of specific SKF and the magnitude of thickness variation by the anatomical site (i.e., the smaller the variation, the better the CRF). Considering the relevance of specific SKF for CRF, their further use would be recommended for monitoring physical fitness in soccer players.